2018
DOI: 10.1016/j.bjae.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia for lung volume reduction surgery and endobronchial valves

Abstract: , whose special interests include anaesthesia for thoracic and upper gastrointestinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Eventually the National Emphysema Treatment Trial (NETT) formally assessed the safety, efficacy, risk/benefit ratio, and cost effectiveness of LVRS. 24 The results suggested that LVRS offered no survival benefit over those on maximal medical therapy overall, but appeared to improve quality of life, dyspnoea, and exercise tolerance in some patients. Patients who derive the most benefit have low baseline exercise capacity and 'heterogeneous' emphysema with predominantly upper lobe disease with relatively unaffected lung tissue in other areas.…”
Section: Assessing Suitability For Lung Volume Reduction Surgerymentioning
confidence: 95%
See 1 more Smart Citation
“…Eventually the National Emphysema Treatment Trial (NETT) formally assessed the safety, efficacy, risk/benefit ratio, and cost effectiveness of LVRS. 24 The results suggested that LVRS offered no survival benefit over those on maximal medical therapy overall, but appeared to improve quality of life, dyspnoea, and exercise tolerance in some patients. Patients who derive the most benefit have low baseline exercise capacity and 'heterogeneous' emphysema with predominantly upper lobe disease with relatively unaffected lung tissue in other areas.…”
Section: Assessing Suitability For Lung Volume Reduction Surgerymentioning
confidence: 95%
“…Lung volume reduction surgery (LVRS) is performed as a palliative procedure for patients with severe COPD caused by emphysema. 24 It is usually performed via a video-assisted thoracic surgery approach and typically involves a wedge excision of emphysematous lung tissue. LVRS is thought to benefit patients with emphysema by improving elastic recoil of the remaining lung, reducing chest hyperinflation so improving respiratory muscle efficiency, and by reducing the intrathoracic pressure thus improving ventricular filling as a consequence of reduced dynamic hyperinflation.…”
Section: Assessing Suitability For Lung Volume Reduction Surgerymentioning
confidence: 99%
“…The role of the MDT for LVRS is to ensure selection criteria are met, that patients are appropriately optimised from a medical point of view and that techniques most suited to individual patients are considered (2). The pathway should also ensure that those patients not suitable for surgery or endobronchial valve insertion are able to access ongoing research studies with alternative therapies.…”
Section: Introductionmentioning
confidence: 99%